Strategi Pengembangan Pariwisata Halal Di Propinsi Sumatera Utara - Y Yusrizal; Sudirman Suparmin (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2018)
Basically the development of sharia tourism is not an exclusive tour because non-Muslim tourists can also enjoy Islamic ethical services. Sharia tourism not only to existence of pilgrimage and religious tourist attractions, but also includes the availability of supporting facilities, for example, restaurants and hotels that provide halal food and prayer places. Tourist products and services, as well as tourist destinations in sharia tourism are the same as general tourism as long as they do not conflict with Islamic values and ethics. This study aims to formulate a strategy model for the development of halal Pariariata in North Sumatra Province, especially for Medan and Parapat City. This research type used survey research for this study. Data analysis in this study is qualitative analysis in general and SWOT analysis. Qualitative analysis is generally directed at data from the results of discussions, observations, and interviews by collecting and analyzing data simultaneously, writing notes during and after data collection, encoding to simplify data, writing reasoning on data, and developing concepts and connections analysis results with the existing literature. The results of the study for the city of Medan are already ready as sharia tourist destinations for aspects of attractions (because they have started to hold sharia tour packages and events), amenities (except hotels and spas which some do not have halal certification) and institutions. Optimization of Medan City as a Sharia tourist destination requires several improvements, especially in institutional aspects, especially the readiness of human resources. And clear regulations from the city government of Medan, for the City of Parapat not optimal enough to work on Halal tourism. But still need commitment and consistency in working on Halal tourism in the city of Parapat